Cholemic Nephropathy Causes Acute Kidney Injury and Is Accompanied by Loss of Aquaporin 2 in Collecting Ducts. Issue 5 (14th March 2019) - Bräsen, Jan Hinrich; Mederacke, Young‐Seon; Schmitz, Jessica; Diahovets, Kateryna; Khalifa, Abedalrazag; Hartleben, Björn; Person, Fermín; Wiech, Thorsten; Steenbergen, Eric; Großhennig, Anika; Manns, Michael P.; Schmitt, Roland; et al.
Abstract : Impairment of renal function often occurs in patients with liver disease. Hepatorenal syndrome is a significant cause of acute kidney injury (AKI) in patients with cirrhosis (HRS‐AKI, type 1). Causes of non‐HRS‐AKI include cholemic nephropathy (CN), a disease that is characterized by intratubular bile casts and tubular injury. As data on patients with CN are obtained primarily from case reports or autopsy studies, we aimed to investigate the frequency and clinical course of CN. We identified 149 patients who underwent kidney biopsy between 2000 and 2016 at the Department of Gastroenterology, Hepatology and Endocrinology at Hannover Medical School. Of these, 79 had a history of liver disease and deterioration of renal function. When applying recent European Association for the Study of the Liver criteria, 45 of 79 patients (57%) presented with AKI, whereas 34 patients (43%) had chronic kidney disease (CKD). Renal biopsy revealed the diagnosis of CN in 8 of 45 patients with AKI (17.8%), whereas none of the patients with CKD was diagnosed with CN. Univariate analysis identified serum bilirubin, alkaline phosphatase, and urinary bilirubin and urobilinogen as predictive factors for the diagnosis of CN. Histological analysis of AKI patients with normal bilirubin, elevated bilirubin, and the diagnosis of CN revealed loss of aquaporin 2 (AQP2) expression in collecting ducts in patients with elevated bilirubin and CN. Biopsy‐related complications requiring medical intervention occurred in 4 of 79 patients (5.1%). Conclusion : CN is a common finding in patients with liver disease, AKI, and highly elevated bilirubin. Loss of AQP2 in AKI patients with elevated bilirubin and CN might be the result of toxic effects of cholestasis and in part be responsible for the impairment of renal function.